Type II antithrombin deficiency caused by a novel missense mutation (p.Leu417Gln) in a Chinese family. Issue 1 (January 2021) - Liu, Siqi; Wang, Huanhuan; Xu, Qiyu; Luo, Shasha; Jin, Yanhui; Yang, Lihong; Wang, Mingshan
Abstract : The aim of the report was t: o explore the phenotype and genotype of a hereditary antithrombin deficient Chinese family. Functional and molecular analysis of the proband and his family members was performed. Online bioinformatics software was used to predict the pathogenicity of the novel mutation. ClustalX-2.1-win and PyMol software were applied to conservative analysis and generate molecular graphic images, respectively. Functional analysis had shown that the antithrombin (AT):A of the proband was reduced to 32% whereas AT:Ag was normal. Molecular analysis revealed a heterozygous missense mutation p. Leu417Gln in exon 7 of SERPINC1 gene. Bioinformatics and model analysis indicated that this mutation could affect the integrity of local intermolecular structures, resulting in a mild type of antithrombin deficiency but when combined with other genetic or acquired thrombophilic factors, patients may develop venous thrombosis. The p.Leu417Gln mutation was responsible for the decrease of AT:A in this family and caused type II antithrombin deficiency.